Diseminasi informasi zero waste oleh Yayasan Pengembangan Biosains dan Bioteknologi - Umy Fatkhah; Yunus Winoto; Ute Lies Siti Khadijah (Jurnal Kajian Informasi dan Perpustakaan, 2020)
The Bioscience and Biotechnology Development Foundation (YPBB) managing organic and non organic waste through a program called zero-waste. This study aimed to determine the zero waste information dissemination activities at YPBB. The study used a qualitative method with a case study approach. Data collection techniques used were observations, interviews, and document analysis. The analysis was performed by data reduction, data presentation, and concluding. Study results indicated that zero-waste information dissemination activities were through Programs Zero-Waste Lifestyle (ZWL) and Zero-Waste Cities (ZWC). The ZWL Program comprised training involving partners. Communicators in the ZWL Program were YPBB voluntary trainers, that the message conveyed was informative, using a clear and to understands word approach and a humorous approach. The media used presentation slides as instructional media, organic nonorganic waste, takakura, and biopore drills as instructional aids. The ZWL Program participants were middle and upper-middle urban communities. The kelurahan or RW implemented the Zero Waste Cities Program (ZWC). Communicators in this program were RW heads and cadres, that give messages were persuasive and educational, conveyed through posters and WhatsApp groups. The study concludes that the dissemination of zero waste information through the Zero-Waste Lifestyle (ZWL) and Zero Waste Cities (ZWC) Programs are viewed from communication elements, namely communicators, messages, media and communication elements that are already running and by the program planned. The conclusion this research shows that the dissemination of zero waste information through ZWL and ZWC according to the communication element is already in progress, and according to the planned program.